Critical study of baselines used in the analysis of striated muscle, chemical methodology and normal values ​​in humans - Marchena, Carlos R. (1962)
In this paper, systematically describes the technology developed in this laboratory for the analysis of skeletal muscle, taken as an expression of the cellular phase of the organism, which is a great tool for future research on the changes that would occur in the intracellular environment during various pathological processes, or in many other biological problems. In our particular case, and as part of the curriculum of renal failure, we want to establish if it means intracellular biochemical changes, as with the extracellular environment, or whether its composition is more or less independent of renal function.